PERAN PAGUYUBAN PEMULUNG WANITA DI TPSP PIYUNGAN, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Zulianti, Zulianti (Natapraja, 2017)
The purpose of this research is to examine the activity of women scavengers community in TPSP Piyungan and the role of community for member of women scavengers community in TPSP Piyungan. Data analysis technique on this research was descriptive analyzis Primary data retrieval techniques used in-depth interviews. The result of this research revealed there are about 210 (two hundred and ten) female scavengers on TPSP Piyungan who came from Bantul Regency, Gunungkidul Regency, Yogyakarta Municipality, Grobogan Regency and Pati Regency and all of them are married. Community helds regular meetings once a week and conducts savings and loan activities for members of the community. For every loan about Rp 1,000,000, the member should pay loan service of Rp 25,000 / week. Moreover they have to pay 50 % fines of total savings if the borrower does not pay for four consecutive installments. The distribution of residual income is divided into members proportionally after deducting the services of the management amounting to 0.5% of the total loan services. Savings and loan management in paguyuban is traditional, based on trust. Keywords: Community, Female Scavenger, and Savings and Loan